On the Evaluation of Solar Greenhouse Efficiency in Building Simulation during the Heating Period - Francesco Asdrubali; Franco Cotana; Antonio Messineo (Energies, 2012)
Among solar passive systems integrated in buildings, sunspaces or solar greenhouses represent a very interesting solution. A sunspace is a closed, southbound volume, constituted by transparent surfaces, adjacent to a building, which reduces winter energy demand thanks to the use of solar gains. The effect of a typical solar greenhouse on the energy balance of a building was evaluated during the heating period with two stationary procedures (Method 5000 and EN ISO 13790) and with a dynamic tool (TRNSYS). After the analysis of the greenhouse alone, the behavior of an entire house was simulated; a flat equipped with a sunspace, recently built thanks to public contributions provided by the Umbria Region in Italy to widespread bio-climatic architecture, was used as case-study. Simulations were carried out for the examined flat, both with a steady-state tool and with a dynamic one; the contribution of the sunspace was estimated thanks to the various methods previously mentioned. Finally, the simulated data were satisfactorily compared with the real energy consumptions (natural gas for heating) of the flat; the sunspace allows a reduction of winter energy demand of the flat of about 20%.